Model nuclear energy density functionals derived from ab initio calculations. (6th July 2020) - Salvioni, G; Dobaczewski, J; Barbieri, C; Carlsson, G; Idini, A; Pastore, A
Abstract: We present the first application of a new approach, proposed in (2016 J . Phys . G : Nucl . Part . Phys . 43 04LT01) to derive coupling constants of the Skyrme energy density functional (EDF) from ab initio Hamiltonian. By perturbing the ab initio Hamiltonian with several functional generators defining the Skyrme EDF, we create a set of metadata that is then used to constrain the coupling constants of the functional. We use statistical analysis to obtain such an ab initio -equivalent Skyrme EDF. We find that the resulting functional describes properties of atomic nuclei and infinite nuclear matter quite poorly. This may point to the necessity of building up the ab initio -equivalent functionals from more sophisticated generators. However, we also indicate that the current precision of the ab initio calculations may be insufficient for deriving meaningful nuclear EDFs.